Disparities in pancreatic cancer care and research in Native Americans: Righting a history of wrongs. Issue 8 (8th February 2022) - Kills First, Claymore C.; Sutton, Thomas L.; Shannon, Jackilen; Brody, Jonathan R.; Sheppard, Brett C.
Abstract : Disparities in pancreatic cancer incidence and outcomes exist in Native American populations. These disparities are multifactorial, difficult to quantify, and are influenced by historical, socioeconomic, and health care structural factors. The objective of this article was to assess these factors and offer a call to action to overcome them. The authors reviewed published data on pancreatic cancer in Native American populations with a focus on disparities in incidence, outcomes, and research efforts. The historical context of the interactions between Native Americans and the United States health care system was also analyzed to form actionable items to build trust and collaboration. The incidence of pancreatic cancer in Native Americans is higher than that in the general US population and has the worst survival of any major racial or ethnic group. These outcomes are influenced by a patient population with often poor access to high‐quality cancer care, historical trauma potentially leading to reduced care utilization, and a lack of research focused on etiologies and comorbid conditions that contribute to these disparities. A collaborative effort between nontribal and tribal leaders and cancer centers is key to addressing disparities in pancreatic cancer outcomes and research. More population‐level studies are needed to better understand the incidence, etiologies, and comorbid conditions of pancreatic cancer in Native Americans. Finally, a concerted, focused effort should be undertaken between nontribal and tribal entities to increase the access of Native Americans to high‐quality care for pancreatic cancer and other lethal malignancies. Abstract : More population‐level studies are needed to better understand the incidence, etiologies, and comorbid conditions of pancreatic cancer in Native Americans. A concerted, focused effort should be undertaken between nontribal and tribal entities to increase the access of Native Americans to high‐quality care for pancreatic cancer and other lethal malignancies.